Atypical function of a centrosomal module in WNT signalling drives contextual cancer cell motility - Yi Luo; Miriam Barrios-Rodiles; Gagan D. Gupta; Ying Y. Zhang; Abiodun A. Ogunjimi; Mikhail Bashkurov; Johnny M. Tkach; Ainsley Q. Underhill; Liang Zhang; Mohamed Bourmoum; Jeffrey L. Wrana; Laurence Pelletier (Nature Communications)
Abstract Centrosomes control cell motility, polarity and migration that is thought to be mediated by their microtubule-organizing capacity. Here we demonstrate that WNT signalling drives a distinct form of non-directional cell motility that requires a key centrosome module, but not microtubules or centrosomes. Upon exosome mobilization of PCP-proteins, we show that DVL2 orchestrates recruitment of a CEP192-PLK4/AURKB complex to the cell cortex where PLK4/AURKB act redundantly to drive protrusive activity and cell motility. This is mediated by coordination of formin-dependent actin remodelling through displacement of cortically localized DAAM1 for DAAM2. Furthermore, abnormal expression of PLK4, AURKB and DAAM1 is associated with poor outcomes in breast and bladder cancers. Thus, a centrosomal module plays an atypical function in WNT signalling and actin nucleation that is critical for cancer cell motility and is associated with more aggressive cancers. These studies have broad implications in how contextual signalling controls distinct modes of cell migration.